1994
DOI: 10.1002/j.1460-2075.1994.tb06771.x
|View full text |Cite
|
Sign up to set email alerts
|

Sialoadhesin, a macrophage sialic acid binding receptor for haemopoietic cells with 17 immunoglobulin-like domains.

Abstract: Sialoadhesin is a macrophage‐restricted adhesion molecule of 185 kDa that mediates sialic acid‐dependent binding to cells. It is expressed strongly by macrophages in lymphoid and haemopoietic tissues where it is likely to mediate cell‐cell interactions. Here we report the molecular cloning of murine sialoadhesin and show that it is a new member of the immunoglobulin (Ig) superfamily with 17 Ig‐like domains. COS cells transfected with a cDNA encoding full‐length sialoadhesin bound mouse bone marrow cells in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
183
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 255 publications
(187 citation statements)
references
References 68 publications
4
183
0
Order By: Relevance
“…It is the largest transmembrane member of the immunoglobulin super family (IgSF) with an extracellular domain made up of 17 immunoglobulin domains. Since it lacks tyrosine binding signaling motifs within its cytoplasmic domain and this domain is poorly conserved, it is likely that its primary function is more to serve as a binding partner for appropriate ligands and involved in cell adhesion and functions such as serving as a phagocyte receptor [42]. It has also been implicated in influencing T cell function and activation [43].…”
Section: Discussionmentioning
confidence: 99%
“…It is the largest transmembrane member of the immunoglobulin super family (IgSF) with an extracellular domain made up of 17 immunoglobulin domains. Since it lacks tyrosine binding signaling motifs within its cytoplasmic domain and this domain is poorly conserved, it is likely that its primary function is more to serve as a binding partner for appropriate ligands and involved in cell adhesion and functions such as serving as a phagocyte receptor [42]. It has also been implicated in influencing T cell function and activation [43].…”
Section: Discussionmentioning
confidence: 99%
“…Sialoadhesin (Sn), also designated Siglec-1 or CD169, is the prototypic member of the siglec family of sialic acid binding Ig-like lectins (Crocker et al, 1994). Other members of this family are CD22, MAG.…”
Section: Sialoadhesin (Sn)mentioning
confidence: 99%
“…It is expressed only on resident macrophage subpopulations (Crocker et al, 1994), and cell binding studies have shown that, among hemopoietic cells, it binds preferentially to granulocytes . In the bone marrow, Sn is found selectively at contact sites with developing myeloid cells (Crocker et al, 1990(Crocker et al, , 1991, and it has been suggested that, in lymphoid tissues, it acts as a lymphocyte adhesion molecule (Van den Berg et al, 1992).…”
mentioning
confidence: 99%
“…In the bone marrow, Sn is found selectively at contact sites with developing myeloid cells (Crocker et al, 1990(Crocker et al, , 1991, and it has been suggested that, in lymphoid tissues, it acts as a lymphocyte adhesion molecule (Van den Berg et al, 1992). On the basis of sequence analysis, Sn has been shown to be a member of the immunoglobulin superfamily (IgSF) (Williams & Barclay, 1988;Williams et al, 1989) consisting of 17 immunoglobulin-like domains, a membrane-spanning helix, and a short cytoplasmic domain (Crocker et al, 1994). The immunoglobulin domains are arranged in a linear array made up of 16 C2-set domains and one N-terminal, membrane distal, V-set domain.…”
mentioning
confidence: 99%
See 1 more Smart Citation